The Design of Interactive Multimedia as an Educational Medium for Introducing the History of Indonesian Currency to Children Aged 10-17 Years - Jovan Dwiza Pratama; Bangkit Sanjaya (Fakultas Bahasa dan Seni Universitas Negeri Medan, 2026)
The interest of students in learning history, particularly the history of Indonesian currency, remains relatively low when the material is delivered through conventional methods. Consequently, this study aims to design an interactive multimedia learning medium titled “Mengenal Rupiah” to support adolescents’ comprehension of the history of the rupiah as a national economic identity. The multimedia design process encompasses pre-production, production, and post-production stages. Data collection techniques employed included observation, interviews, and questionnaires administered to 17 respondents aged 10–17 years in Semarang City, selected through purposive sampling. The data were analyzed using a qualitative descriptive approach to ascertain the needs and preferences for digital learning media among the target users. The findings of the data analysis reveal that students exhibit greater interest in learning the history of currency through illustrative visualizations, animation, and interactivity compared to textbook-based methods. Based on these findings, the “Mengenal Rupiah” media was developed utilizing Procreate and Adobe Animate with user-friendly interactive navigation. This work applies visual communication design principles with an edutainment concept to create an engaging learning experience. As a prototype, this media still possesses limitations and holds the potential for further development into a more comprehensive and interactive learning medium.